Peri-Ocular and Facial Multiple Hereditary Infundibulocystic Basal Cell Carcinoma (MHIBCC) - Siddiqui, R Janjua, QK Ali, A P (Pakistan Journal of Ophthalmology, 2008)
Purpose: To report two cases of Multiple hereditary infundibulocystic basal cell carcinoma (MHIBCC) in two successive generations of a family and to discuss its management. Design and Methodology: This an observational case report in an institutional setting, reporting on two patients of successive generations referred by the department of dermatology. Clinical management: Both patients had cosmetically noticeable lesions for a very long time and did not look like typical basal cell carcinomas. Due to uncertain clinical diagnosis biopsies were taken and on the basis of differing results, a controversy of was stirred up. Histological slides and clinical photographs were sent for second opinion whereby, a definitive diagnosis was reached. Conclusions: Combination of minimally invasive surgery, cryotherapy and observation should form the basis of clinical and surgical management. This saves the patient from aggressive and unnecessary surgery that can be disfiguring. This is a diagnosis which should be kept at the back of one’s mind when faced with similar lesions with a family history.